The Proposed Model Of The Integration Of The Principle Of Maqasid Al- Shariah In Managerial Decision Making Process In Shariah-Compliant Securities - Nurul Nadirah Binti Abu Hasan; Khairunnezam Bin Mohd Noor; Zulkifli Abdul Ghani; Ahmed Abdul Malik (Academic Inspired Network (AIN), 2024)
Non-Indexed Publication